2021
DOI: 10.3389/fimmu.2021.630938
|View full text |Cite
|
Sign up to set email alerts
|

AhR Ligands Modulate the Differentiation of Innate Lymphoid Cells and T Helper Cell Subsets That Control the Severity of a Pulmonary Fungal Infection

Abstract: In agreement with other fungal infections, immunoprotection in pulmonary paracoccidioidomycosis (PCM) is mediated by Th1/Th17 cells whereas disease progression by prevalent Th2/Th9 immunity. Treg cells play a dual role, suppressing immunity but also controlling excessive tissue inflammation. Our recent studies have demonstrated that the enzyme indoleamine 2,3 dioxygenase (IDO) and the transcription factor aryl hydrocarbon receptor (AhR) play an important role in the immunoregulation of PCM. To further evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…The number of CD11c + cells expressing membrane (IAb, CD80, CD86) markers was also increased. CH-223191 also augmented the migration of myeloid dendritic cells to the lungs and promoted the expansion of Th17 lymphocytes associated with concomitant reduction of Treg cells, Th1, and Th22 [87,88]. The results strongly suggest that fungal infections can be modulated by AHR signaling, unveiling new perspectives to treat these infections.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…The number of CD11c + cells expressing membrane (IAb, CD80, CD86) markers was also increased. CH-223191 also augmented the migration of myeloid dendritic cells to the lungs and promoted the expansion of Th17 lymphocytes associated with concomitant reduction of Treg cells, Th1, and Th22 [87,88]. The results strongly suggest that fungal infections can be modulated by AHR signaling, unveiling new perspectives to treat these infections.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…AhR expresses innate and adaptive immune cells and can participate in the activation and functional development of the immune system [29]. Th17 and Treg cells, belonging to CD4 + T lymphocytes, play a role in promoting and reducing in ammation in cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Th17/Treg imbalance is involved in the pathogenesis of many autoimmune [30], metabolic [31], and infectious diseases [32]. Therefore, AhR plays an important role in Th17 and Treg cell differentiation and function [17,29] and is involved in Th17/Treg imbalance mechanism. However, the immunopathogenic role (especially Th17/Treg balance) of AhR in CHB remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Eliseu et al. reported that both AhR agonist Kyn and AhR antagonist CH223191 decreased the number of Th1 cells in a mice pulmonary fungal infection model, while agonist FICZ resulted in the expansion of all CD4+ T cell subsets (Th1, Th2, Th17, Th22, and Treg) ( 65 ). In addition, AhR-deficient mice displayed a decrease in Th1, Th22, and other immune cells in their lungs ( 66 ).…”
Section: Relevance Of Ahr To Immune Cellsmentioning
confidence: 99%